Driving Sustainable Civil Engineering Projects: The Role of Digitalisation and Circular Economy - Hlengiwe Vilakazi; Douglas Aghimien (SureBuilt Series, 2026)
Sustainability problems in South Africa have been exacerbated by urbanisation, ineffective policy enforcement, and the presence of linear construction approaches. With a desire to achieve sustainability in the Architectural Engineering and Construction (AEC) industry, the ideas of the circular economy (CE) and digitalisation have become vital means of improving project delivery. To this end, the current research analyses the impact of these two concepts on the implementation of sustainable civil engineering projects in South Africa. Quantitative research was conducted using questionnaires, and the data were analysed statistically. The results show that CE practices are used primarily at the construction stage, where material recycling, waste reduction, and prefabrication are the most common. At the same time, approaches such as LCA and modularisation are still not widely implemented. Furthermore, digital tools that can contribute to the efficient implementation of CE were identified, as well as obstacles related to the practical use of these two concepts. The study concludes that CE and digitalisation form an effective duo for achieving sustainability in civil engineering projects in South Africa. Integrating Energy and Water Efficiency in Hotel Buildings: A Nexus-Based Assessment from Ghana Rosemary Cobbinah1*, Daniel Yaw Addai Duah2, Gloria Osei - Poku3, Veronica Sakyi Adjei2,